The Malaysian economy structures and dependence - Khor, Martin Kok Peng (Institut Masyarakat, 2019)
It is generally understood that colonial economies are dependent ones, i.e. they rely on some input of external labour and, usually, capital and their markets are restricted, to a lesser or greater extent, by a more dominant and global colonial market. In this book, the author examines the extent to which this was true in colonial Malaya and how, if at all, it was transformed as a result of independence in 1957.